2020
DOI: 10.3390/proteomes8030024
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of Inflammatory Proteins in Plasma of HIV-1-Infected Children Receiving Antiretroviral Therapy

Abstract: Treatment of HIV-1-infected patients results in improved clinical and immunological conditions, but severe non-AIDS-related conditions still persist. Novel proteomic platforms have identified inflammatory proteins where abundance is dysregulated in adult treated patients, whereas limited data are available in treated HIV-1 infection of children. Using a proteomic plasma profiling approach comprising 92 inflammation-related molecules, we analyzed specimens from 43 vertically HIV-1-infected children receiving an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 42 publications
0
13
1
Order By: Relevance
“…Another study using a cohort of PLHIV with dyslipidemia (n = 89) and HC (n = 46) also showed little overlap with our results, with only four inflammatory proteins (4E-BP1, ADA, TNFSF14, and CD40) overlapping with our results (FDR<0.05, same direction) ( deFilippi et al., 2020 ). Of note, a study using 43 children with HIV infection and matched controls showed 15 proteins being downregulated in children with HIV infection compared to HC (FDR<0.01), with none of the proteins being identified in a similar direction compared to our study ( Lemma et al., 2020 ). These differences between studies can be attributed to different cohort characteristics, especially the ethnicities, number of participants, proteins tested, and analysis strategies.…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…Another study using a cohort of PLHIV with dyslipidemia (n = 89) and HC (n = 46) also showed little overlap with our results, with only four inflammatory proteins (4E-BP1, ADA, TNFSF14, and CD40) overlapping with our results (FDR<0.05, same direction) ( deFilippi et al., 2020 ). Of note, a study using 43 children with HIV infection and matched controls showed 15 proteins being downregulated in children with HIV infection compared to HC (FDR<0.01), with none of the proteins being identified in a similar direction compared to our study ( Lemma et al., 2020 ). These differences between studies can be attributed to different cohort characteristics, especially the ethnicities, number of participants, proteins tested, and analysis strategies.…”
Section: Discussioncontrasting
confidence: 42%
“…Assessment of the profile of plasma inflammatory proteins allows the study of complex biological pathways that may lead to the identification of novel therapeutic targets and disease biomarkers. Previous studies that assessed plasma protein profiles were limited by small sample size and/or lack of a proper validation cohort ( Babu et al., 2019a , 2019b ; deFilippi et al., 2020 ; Lemma et al., 2020 ; Sperk et al., 2018 ; Vos et al., 2021 ). In addition, other studies included only patients with central obesity and insulin resistance using statins ( deFilippi et al., 2020 ) or children with HIV infection ( Lemma et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Lemma et al. ( 25 ) had the same finding in children. OSM is part of the IL-6 family and is active in multiple cell types where it influences cell differentiation and inflammation ( 37 ).…”
Section: Discussionmentioning
confidence: 58%
“…Lemma et al. ( 25 ) included 43 HIV-positive and 43-HIV negative children with a median age of 60 months from Ethiopia. They found in line with our findings, levels of OSM and TRANCE to be significantly lower in HIV-positive participants.…”
Section: Discussionmentioning
confidence: 99%
“…HIV-1 causes dysregulation of the innate immune system, persistent immune activation, dysfunction of the inflammatory response and immune system aging (senescence) early in HIV-1 infection. Successful ART ameliorates, but does not completely correct the major immune dysfunctions [ 2 , 3 , 4 , 5 , 6 ], substantial immunological impairment pertains even on the background of the successful ART [ 7 , 8 ] (for the latest review, see [ 9 ]). Hyper-immunoactivation and inflammation persisting in PLWH is recognized as a major cause of HIV-1 associated malignances.…”
Section: Introductionmentioning
confidence: 99%